Freunde Roms und Völker der Finsternis Die Konstruktion von Anderen im päpstlichen Rom des - Gantner, Clemens (2014)
In the eighth and ninth centuries, the papacy had to deal with with a multitude of 'others' aunder variing circumstances. This book reseraches three cases that have had a considerable impact on the papacy: the representation of the Byzantine or 'Greek' empire and the communication with and about the Lombards and the Franks, both in the eighth century, as well as the conflict with Muslim groups called Saracens in the ninth century.